THE OPPORTUNITIES OF PANCASILA AND CIVIC EDUCATION (PPKN) AS AN INSTRUMENT TO BUILD OF STUDENTS' ENVIRONMENTAL CARING CHARACTER - Faisal, Emil El; Sulkipani, Sulkipani (Sriwijaya University Learning and Education International Conference, 2018)
This literature study aims to analyze the opportunity of PPKn as an instrument of development of students' caring character. Caring for the environment is a very influential factor in maintaining the balance and environmental sustainability. The implication is that when humans have a strong concern for the environment then people will feel the great benefits in carrying out activities of life. Conversely, when humans have no concern for the environment, natural disasters will occur as a result of environmental imbalances. Thus, building a care-minded environment is a preventive effort so that environmental damage can be anticipated. Among the preventive efforts are through PPKn. PPKn as one of the subjects developed at the level of schooling has great opportunities and responsibilities in building students' caring character. It can be known from the nature of PPKn as character education. The government has set the policy direction of strengthening character education is to develop the character of students, one of which is the character of environmental care.